Listen-and-repeat training improves perception of second language vowel duration: Evidence from mismatch negativity (MMN) and N1 responses and behavioral discrimination - Saloranta Antti; Alku Paavo; Peltola Maija S. (Elsevier BV, 2022)
The purpose of this study was to examine the efficacy of three days of listen-and-repeat training on the perception and production of vowel duration contrasts. Generalization to an untrained vowel and a non-linguistic sound was also examined. Twelve adults underwent four sessions of listen-and-repeat training over two days with the pseudoword contrast /tite/-/ti:te/. Generalization effects were examined with another vowel contrast, /tote/-/to:te/ and a sinusoidal tone pair as a non-linguistic stimulus. Learning effects were measured with psychophysiological (EEG) event-related potentials (mismatch negativity and N1), behavioral discrimination tasks and production tasks. The results showed clear improvement in all perception measurements for the trained stimuli. The effects also affected the untrained vowel by eliciting an N1 response, and affected the behavioral perception of the non-linguistic stimuli. The MMN response for the untrained linguistic stimuli, however, did not increase. These findings suggest that the training was able to increase the sensitivity of preattentive auditory duration discrimination, but that phoneme-specific spectral information may also be needed to shape the neural representation of phoneme categories.